Tanzanian Coral Reef in Peril, are we Fighting a Losing Battle? - Nsajigwa Emmanuel Mbije (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
Coral reefs are of major importance to the livelihoods of coastal communities and therefore deserve special consideration. While covering less than 1% of the oceanic area, they support almost one third of marine fish species, providing around 10% of the total fish consumed by humans worldwide. Furthermore, coral reefs protect the shoreline and coastal land against ocean waves or surge effects; promote the growth of mangroves and sea grasses by enhancing sediment deposition and stability. Erosion processes of reef structures results in the generation of sand, which is moved and accreted onto the beaches. Reefs provide three dimensional structural frameworks with lots of micro and macro spaces. As a result, coral reefs act as focal points for primary and secondary production. Coral reefs contribute greatly in the maintenance of biodiversity and genetic library in whole coastal ecosystem. Coral reefs are used as feeding, nursery and/or spawning areas by transient species, thereby providing important biological support or link of many mobile organisms from different coastal habitats. Coral reefs directly support pelagic food webs through export of organic production to the adjacent ocean. Furthermore, coral reefs are net sinks for Carbon, principally as calcium carbonate (CaCO3) accretion; hence contribute positively to climate change balance. Certain massive reef-building corals (e.g., massive Porites) contain a wealth of historical proxy climate and environmental information (e.g., temperature, pollution, salinity) locked in their calcium carbonate skeletons.. The socio-economic values of coral reefs are realised mainly through coastal fisheries and coastal tourism. Coral reef related ecosystems provide more than 70% of all artisanal fish production. Thus, coral reefs are crucial sources of income, thereby sustaining livelihoods of coastal communities. In Tanzania, coastal fishing communities depend entirely on coral reefs for their livelihood. Artisanal fisheries of Tanzania supply 90% of the animal protein consumed and the primary source of income for the people. Coral reefs face both natural and anthropogenic pressures, it is estimated 20% have been destroyed and more than 20% at high risk and longterm of collapse and if the present rate of destruction continues, 70% of coral reefs will be destroyed worldwide by 2050. The increased stresses and pressure on reefs mainly from climate change, exacerbated by human activities by overexploitation, have led to significant decline in coral reef resources, including fish catches in coastal communities of Tanzania. These impacts are the results of extinctions and damages incurred to Tanzanian reef ecosystems beyond the power for natural repair processes. Both drivers lead to gradual reduction in fish catches over time, impacting rural communities’ livelihoods, further calling for rigorously studying local livelihood adaptation following reef degradation.In order to safeguard benefits or goods and services from coral reefs it is very important to prevent further degradations and encourage sustainable utilization of coral reefs’ resources by setting up appropriate policies, laws and guidelines. Management of coral reefs in Tanzania is tied to the management of fisheries, which is controlled via licensing, policies, laws and regulations. Enforcement of management actions on coral reefs is faced with several policy/legal and institutional challenges: a) Inadequate institutional cooperation, collaboration and exchange of information, b) Law enforcement capacity of Regulatory Authorities, including Local Government Authorities (LGAs), c) Lack of involvement of Financial Institutions in promoting environmental compliance, including sustainable fishing on coral reefs, d) Limited capacity of fishers and businesses to complying with changing laws and standards, and e) Limited government commitments to support coral reef monitoring. This chapter provides an overview of the current coral reef status in Tanzania for the purposed of heighten conservation efforts.